Pengaruh Planned Happenstance terhadap Career Decision Self-Efficacy dengan Career Exploration Behavior sebagai Mediator - Tiza Annisa; Rose Mini Agus Salim (Jurnal Ilmiah Psikologi MIND SET, 2020)
The 4.0 industrial revolution that is taking place in Indonesia has created a changing situation, which has left SMK students confused in choosing careers after graduating from school. This problem can be overcome if students have a career decision self-efficacy (CDSE). This study aims to determine the effect of planned happenstance skills on CDSE mediated by career exploration behavior. This research was conducted on 789 vocational students (399 male students, 390 female students) in the Depok and Jakarta areas. The results showed that the career decision self-efficacy of vocational students was influenced by planned happenstance skills and mediated by career exploration behavior, even with a low level of correlation. Based on the results of this study, career counselors can help vocational students improve career decision self-efficacy by teaching planned happenstance skills.